Novas narrativas para multiplataformas: um estudo sobre jogos de realidade alternada - Correia, Gabriel Costa (Universidade Federal de São Carlos, 2013)
The main goal of this dissertation is to introduce the alternate reality game as a new narrative for multiplatform. By new narratives are understood the forms of storytelling arising from the current development of digital technology; and for multiplatform the variety of means by which the contents of these stories can travel. For this main objective is reached, two main hypotheses are formulated: 1) ARGs are stories for multiple platforms using code-breaking with playful and narrative functions; and 2) they are developed from an intense transtextuality guided by pop mythology that flourished during the twentieth century. Based on this starting point, this thesis will examine two ARGs, Uncertain Zone and Why So Serious?, in a way that it contributes to the hypothesis that Alternate Reality Games are a native narrative form of convergence culture founded on an extensive base of pop culture references. In the chapter dedicated to Uncertain Zone will be listed the various media used during the performance of the ARG, that together with interviews with the developers and testimonials from participants will weave a more descriptive overview of how alternate reality games are composed as multiplatform narratives. In addition, a brief discussion on the playful and narrative functions of the code-breaking in ARGs will be outlined. With Why So Serious? the analysis will focus on the intense transtextuality that alternate reality games establish to what will be called pop mythology in this dissertation and in the relationship between ARGs and market. Incidentally issues related to participatory culture will be raised throughout the text, but without further reflection, since, worth reiterating, the main goal of this thesis is the demonstration of a contemporary narrative form from some elements previously submitted, this form is the alternate reality game.
Keywords: Cinema; Jogos por computador; Transmídia; Narrativa transmidiática; Transtextualidade; Jogo de realidade alternada; Multiplataforma; Novas narrativas; Mitologia pop; Zona incerta; Why so serious?; Batman; Alternate reality game; Multiplatform; New narratives; Transtextuality; Pop mythology; Uncertain zone; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA